Effectiveness of SMS-based interventions in enhancing antenatal care in developing countries: a systematic review - Mats Målqvist; Mahamadou Kante (BMJ Open)
Objectives Pregnant women in low- and middle-income countries (LMICs), including Mali, often face challenges such as limited access to comprehensive health information and services. Mobile health (mHealth) interventions, particularly SMS-based interventions, have shown promise in addressing maternal health challenges. This review aims to provide an overview of existing SMS-based antenatal care (ANC) applications and assess their effectiveness in improving maternal and child health outcomes.Design A systematic literature review was conducted based on updated PRISMA 2020 guidelines.Data sources PubMed, Scopus, Web of Science, Cochrane Library, Association for Information Systems eLibrary, Direct Science and Google Scholar were searched through 25 March 2024.Eligibility criteria Studies that focused on SMS-based interventions designed to improve ANC information and attendance, published in English or French, conducted in LMICs and published between 2014 and 2024 were included. Exclusion criteria eliminated studies that did not report primary outcomes or did not directly involve SMS-based interventions for ANC.Data extraction and synthesis Relevant data were systematically extracted, including study characteristics, intervention details, and outcome measures. The risk of bias was assessed using the Cochrane Risk of Bias tool for randomised trials (RoB 2), the Risk Of Bias In Non-randomised Studies-of Interventions (ROBINS-I) and the Checklist for Reporting the Development and Evaluation of Complex Interventions in Healthcare (CReDECI), depending on the study design. A subgroup analysis was performed to explore variations in outcomes by region and study design.Results The review identified a range of SMS-based interventions (n=12) that differed in target audience, message frequency (weekly, pregnancy stage-oriented) and content (reminders (91.7% of cases, 11/12), educational (75%) and danger signs (16.7%)). Regional analysis highlighted significant research activity in East Africa but with mixed significance levels. The study design analysis revealed that randomised controlled trials yielded the most significant results, with five of eight studies showing full significance, whereas quasi-experimental studies demonstrated consistent but less frequent effectiveness. Implementation tools varied from SMS gateways to custom applications and third-party platforms, with some interventions combining these approaches. SMS interventions positively impacted ANC attendance, maternal health knowledge and behaviours, with effectiveness varying based on the intervention type, content, frequency and implementation approach.Conclusion SMS-based interventions have the potential to enhance ANC in LMICs by providing tailored health information and promoting healthy behaviours. Further research should focus on refining or replicating these interventions and exploring their long-term effects on maternal and child health outcomes, particularly in underrepresented regions.